All-optically stabilized frequency comb. (2nd November 2015) - Okubo, Sho; Gunji, Kenta; Onae, Atsushi; Schramm, Malte; Nakamura, Keisuke; Hong, Feng-Lei; Hattori, Toshiaki; Hosaka, Kazumoto; Inaba, Hajime
Abstract: We present an all-optically stabilized, erbium-doped mode-locked fiber laser with an optically pumped ytterbium-doped fiber. The mode-locked fiber laser has two frequency-control actuators that are pump laser powers for erbium-doped and ytterbium-doped fibers. We investigate the frequency-control characteristics of the mode-locked laser and find that the fixed points for the two actuators are sufficiently apart from each other, realizing the simultaneous phase locking of the repetition and carrier envelope offset frequencies. We describe a long-term frequency measurement of an acetylene-stabilized laser at 1542 nm using an all-optically stabilized frequency comb.